1997
DOI: 10.1002/(sici)1098-2736(199705)34:5<509::aid-tea6>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Why may students fail to learn from demonstrations? A social practice perspective on learning in physics

Abstract: This study was designed to find out why students may fail to learn from teacher demonstrations. In the context of an interpretive study in an Australian senior-year physics course, data were collected to understand the constraints that mediated learning about rotational motion. Over a period of 6 weeks, we gathered observational data, videotapes of classroom transactions, interviews with students and the teacher, and students' notebooks. Our analysis revealed six dimensions that may have prevented students fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 27 publications
3
69
0
5
Order By: Relevance
“…The unexpected outcomes may generate interest and lead to scientific explanations that are constructed between the teacher and students for the observed phenomenon. While there have been past criticisms of the value of demonstrations as a pedagogical tool in science classrooms (see e.g., Roth, McRobbie, Lucas, & Boutonné, 1997;Shepardson, Moje, & Kennard-McClelland, 1994), recent research has found that demonstrations have a positive effect on students' engagement, emotional energy and their learning of science. A study by Milne and Otieno (2007) applied the sociology of emotions to the analysis of classroom conversations and actions during demonstrations, showing that demonstrations elicited greater student engagement and positive emotional energy, more sophisticated use of the symbols associated with chemistry and a willingness from students to move between describing the phenomena and submicroscopic explanations.…”
Section: Demonstrationsmentioning
confidence: 99%
“…The unexpected outcomes may generate interest and lead to scientific explanations that are constructed between the teacher and students for the observed phenomenon. While there have been past criticisms of the value of demonstrations as a pedagogical tool in science classrooms (see e.g., Roth, McRobbie, Lucas, & Boutonné, 1997;Shepardson, Moje, & Kennard-McClelland, 1994), recent research has found that demonstrations have a positive effect on students' engagement, emotional energy and their learning of science. A study by Milne and Otieno (2007) applied the sociology of emotions to the analysis of classroom conversations and actions during demonstrations, showing that demonstrations elicited greater student engagement and positive emotional energy, more sophisticated use of the symbols associated with chemistry and a willingness from students to move between describing the phenomena and submicroscopic explanations.…”
Section: Demonstrationsmentioning
confidence: 99%
“…Harrison and Treagust (1996 also suggested that when students were encouraged to use multiple particle models, their understanding of abstract concepts, e.g., bonding and the structure of an atom, was enhanced. One possible explanation for these findings is that students do not always learn what the teachers intend from demonstrations (Roth, 1997) because they have no opportunity to make predictions and explanations that requires them to connect visual features of representations to relevant concepts (Globert & Clement, 1999).…”
Section: Concrete Models: Visualizing 3d Configurations Of Moleculesmentioning
confidence: 99%
“…Las referencias históricas (Estocolmo, 1972;Tblisi, 1977;Moscú, 1987;Tesalónica, 1997 hannesburgo, 2002; Montreal, 2009) insisten en la idea de que, para lograr los objetivos más relevantes de la educación ambiental, es necesario otorgar un papel activo al alumno en su propio proceso de aprendizaje y, como consecuencia de ello, plantea la necesidad de que el papel del profesorado se caracterice fundamentalmente por crear los ambientes que faciliten ese aprendizaje (Novo, 1998). La naturaleza del ambiente del aula y las interacciones psicosociales determinan la forma en que los estudiantes aprenden y logran sus metas, (Roth, McRobbie, Lucas & Boutonné, 1997). Ello conlleva propiciar la participación directa en la solución de problemas ambientales y que hoy día reclama integrar aspectos tales como los temas sobre desarrollo sustentable, ser una educación socialmente crítica, propiciar procesos participativos y favorecer asociaciones para el cambio (Tilbury, 2001).…”
Section: Hacia Una Educación Sostenibleunclassified